1997
DOI: 10.1104/pp.114.2.583
|View full text |Cite
|
Sign up to set email alerts
|

Regulation of the Accumulation and Reduction of Nitrate by Nitrogen and Carbon Metabolites in Maize Seedlings

Abstract: lhe accumulation and reduction of nitrate in the presence of the nitrogen metabolites asparagine (Asn) and glutamine (Cln) and the carbon metabolite sucrose (Suc) were examined i n maize (Zea mays L.) seedlings in an attempt to separate their effects on the nitrate uptake system and the nitrate reduction system. After 8 h of exposure to nitrate in the presence of 1 mM Asn, tissue nitrate accumulation was reduced at 250 ~L M external nitrate, but not at 5 mM Asn.The induction of nitrate reductase (NR) activity … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
43
0
4

Year Published

2002
2002
2015
2015

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 75 publications
(50 citation statements)
references
References 10 publications
3
43
0
4
Order By: Relevance
“…It has been suggested that glutamate inhibited NR activity in roots, but no inhibition in shoots (Ivashikian and Sokolov, 1997). Sivasankar et al (1997) observed that Gln and asparagine (Asn) inhibited the induction of NR activity in corn roots at both 250 M and 5 mM of external NO 3 -supply. They concluded that inhibition was not the result of altered NO 3 -uptake, and tissue nitrate accumulation was reduced at 250 M external nitrate in the presence of 1 mM Asn, but not at 5 mM Asn.…”
Section: Effect On Nra Nira and Gsamentioning
confidence: 99%
See 3 more Smart Citations
“…It has been suggested that glutamate inhibited NR activity in roots, but no inhibition in shoots (Ivashikian and Sokolov, 1997). Sivasankar et al (1997) observed that Gln and asparagine (Asn) inhibited the induction of NR activity in corn roots at both 250 M and 5 mM of external NO 3 -supply. They concluded that inhibition was not the result of altered NO 3 -uptake, and tissue nitrate accumulation was reduced at 250 M external nitrate in the presence of 1 mM Asn, but not at 5 mM Asn.…”
Section: Effect On Nra Nira and Gsamentioning
confidence: 99%
“…Li et al (1995) also demonstrated that 5 mM glutamine added together with NO 3 − resulted in reduced levels of NR mRNA in both root and shoot of maize. Sivasankar et al (1997) observed that Gln and asparagine (Asn) inhibited the induction of NR activity (NRA) in corn roots at an external supply of 250 M and 5 mM NO 3 − . They concluded that inhibition was not the result of altered NO 3 − uptake, and tissue nitrate accumulation was reduced at 250 M external nitrate in the presence of 1mM Asn, but not at 5mM Asn.…”
Section: Amino Acids and Enzyme Regulationmentioning
confidence: 99%
See 2 more Smart Citations
“…Feeding directly from phloem sap allows aphids to get access to free amino acids that do not require protein digestion before assimilation. This withdrawal could signal depletion of the nitrogen metabolites Asn and Gln (Sivasankar et al, 1997), leading to the observed induction of NiR.…”
Section: Cell Maintenance Genesmentioning
confidence: 99%